Tinjauan Yuridis Terhadap Pembelaan Terpaksa Sebagai Alasan Penghapus Pidana - Muhammad Rizqi Hengki; Khilmatin Maulidah (Fakultas Hukum Universitas Islam Batik Surakarta, 2023)
The Indonesian Criminal Code regulates the reasons for abolishing crimes which are generally divided into two, namely justifying reasons and forgiving reasons. Based on this, this study formulates two problems, namely: 1) What is the juridical review of forced defense as an excuse for criminal punishment? 2) How is the review of juridical defense forced as a reason for the abolition of punishment in the current Criminal Code? This study uses a normative juridical research method. The results of the study show that the juridical arrangements related to reasons for abolishing sentences in the current Indonesian Criminal Code have been explicitly regulated regarding the scope of dividing reasons for abolishing sentences into justification reasons or excuses which previously had not been differentiated between the two, this is an appropriate and more effective reform. so that it is easier for law enforcement officials to apply the theory of criminal abolition reasons. Keywords: Juridical Review, Forced Defense, Reasons for Abolition